Metabolic Capability of a Predominant Halanaerobium sp. in Hydraulically Fractured Gas Wells and Its Implication in Pipeline Corrosion - Liang, Renxing; Davidova, Irene A.; Marks, Christopher R.; Stamps, Blake W.; Harriman, Brian H.; Stevenson, Bradley S.; Duncan, Kathleen E.; Suflita, Joseph M. (Frontiers in Microbiology, 2016)
Microbial activity associated with produced water from hydraulic fracturing operations can lead to gas souring and corrosion of carbon-steel equipment. We examined the microbial ecology of produced water and the prospective role of the prevalent microorganisms in corrosion in a gas production facility in the Barnett Shale. The microbial community was mainly composed of halophilic, sulfidogenic bacteria within the Order Halanaerobiales, which reflected the geochemical conditions of highly saline water containing sulfur species (S2O32-, SO42- and HS-). A predominant, halophilic bacterium (strain DL-01) was subsequently isolated and identified as belonging to the genus Halanaerobium. The isolate could degrade guar gum, a polysaccharide polymer used in fracture fluids, to produce acetate and sulfide in a 10% NaCl medium at 37 oC when thiosulfate was available. To mitigate potential deleterious effects of sulfide and acetate, a quaternary ammonium compound was found to be an efficient biocide in inhibiting the growth and metabolic activity of strain DL-01 relative to glutaraldehyde and tetrakis (hydroxymethyl) phosphonium sulfate. Collectively, our findings suggest that predominant halophiles associated with unconventional shale gas extraction could proliferate and produce sulfide and acetate from the metabolism of polysaccharides used in hydraulic fracturing fluids. These metabolic products might be returned to the surface and transported in pipelines to cause pitting corrosion in downstream infrastructure.